Crosstalk Between MLO‐Y4 Osteocytes and C2C12 Muscle Cells Is Mediated by the Wnt/β‐Catenin Pathway. (4th October 2017) - Huang, Jian; Romero‐Suarez, Sandra; Lara, Nuria; Mo, Chenglin; Kaja, Simon; Brotto, Leticia; Dallas, Sarah L; Johnson, Mark L; Jähn, Katharina; Bonewald, Lynda F; Brotto, Marco
Abstract: We examined the effects of osteocyte secreted factors on myogenesis and muscle function. MLO‐Y4 osteocyte‐like cell conditioned media (CM) (10%) increased ex vivo soleus muscle contractile force by ∼25%. MLO‐Y4 and primary osteocyte CM (1% to 10%) stimulated myogenic differentiation of C2C12 myoblasts, but 10% osteoblast CMs did not enhance C2C12 cell differentiation. Because WNT3a and WNT1 are secreted by osteocytes, and the expression level of Wnt3a is increased in MLO‐Y4 cells by fluid flow shear stress, both were compared, showing WNT3a more potent than WNT1 in inducing myogenesis. Treatment of C2C12 myoblasts with WNT3a at concentrations as low as 0.5 ng/mL mirrored the effects of both primary osteocyte and MLO‐Y4 CM by inducing nuclear translocation of β‐catenin with myogenic differentiation, suggesting that Wnts might be potential factors secreted by osteocytes that signal to muscle cells. Knocking down Wnt3a in MLO‐Y4 osteocytes inhibited the effect of CM on C2C12 myogenic differentiation. Sclerostin (100 ng/mL) inhibited both the effects of MLO‐Y4 CM and WNT3a on C2C12 cell differentiation. RT‐PCR array results supported the activation of the Wnt/β‐catenin pathway by MLO‐Y4 CM and WNT3a. These results were confirmed by qPCR, showing upregulation of myogenic markers and two Wnt/β‐catenin downstream genes, Numb and Flh1 . We postulated that MLO‐Y4 CM/WNT3a could modulate intracellular calcium homeostasis as the trigger mechanism for the enhanced myogenesis and contractile force. MLO‐Y4 CM and WNT3a increased caffeine‐induced Ca 2+ release from the sarcoplasmic reticulum (SR) of C2C12 myotubes and the expression of genes directly associated with intracellular Ca 2+ signaling and homeostasis. Together, these data show that in vitro and ex vivo, osteocytes can stimulate myogenesis and enhance muscle contractile function and suggest that Wnts could be mediators of bone to muscle signaling, likely via modulation of intracellular Ca 2+ signaling and the Wnt/ β‐Catenin pathway. © 2017 American Society for Bone and Mineral Research